Traumatization and mental distress in long-term prisoners in Europe - Dudeck, Manuela; Barnow, Sven (Punishment & society, 2011)
This article investigates the prevalence of traumatization and mental distress in a sample of 1055 male European long-term prisoners as part of a wider study of the living conditions of prisoners serving sentences of at least five years in Belgium, Croatia, Denmark, England, Finland, France, Germany, Lithuania, Poland, Spain and Sweden. Data were collected in a written survey using the Posttraumatic Diagnostic Scale (PDS), the Brief Symptom Inventory (BSI) as well as questions on attempted suicide and auto-aggressive behaviour. Participants experienced a mean of three traumatic events, with 14 per cent developing a Posttraumatic Stress Disorder (PTSD) subsequently. In each national sample, more than 50 per cent of the participants were in need of treatment because of psychological symptoms and nearly one-third had attempted suicide.